PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 2 BAYANG - Yenti, Novida - (Pendidikan Biologi, 2014)
This research was conducted due to the studentsâ low learning achievement in Biology. The students who did not master the learning materials, were less involved in the learning process, had low learning intererest, and were passive and less motivated to learn were some factors tringgering the occurrence of the problem. The purpose of this research was to see the application of Two Stay Two Stray cooperative learning model on the studentsâ Biology learning achievement in class XI of SMAN 2 Bayang. This was an experimental research which used Randomized Control-Group Posttest Only Design. By using purposive Sampling Technique, class XI IPA 3 was chosen as the experimental class, and class XI IPA 1 was as the control class. The data which had been tested its normality and homogeneity was analyzed by using t-test. Based on the result of post-test, it was known that the average score of the students in the experimental class was 81,27, and in the control class was 71,05. Further, the value of tcaltulted (3,66) was higher than ttable (1,67) indicating that the hypothesis was accepted on the significance level 95% (Î± = 0,05). Therefore, it was concluded that the use of Two Stay Two Stray cooperative learning model could improve the studentsâ Biology learning achievement in class XI of SMAN 2 Bayang.